The architecture of the self-organizing long term evolution networks - Kovalenko, A. I.; Shelkovnikov, B. N.; Zhukov, R. V. (Видавництво Львівської політехніки, 2010)
Within this article the models of the selforganizing long term evolution (LTE) networks (SON) were explored.
Keywords: SON; LTE